2009
DOI: 10.1002/j.2168-9830.2009.tb01007.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Worked‐Example Instruction in Electrical Engineering: The Role of Fading and Feedback during Problem‐Solving Practice

Abstract: How can we help college students develop problem-solving skills in engineering? To answer this question, we asked a group of engineering freshmen to learn about electrical circuit analysis with an instructional program that presented different problem-solving practice and feedback methods. Three findings are of interest. First, students who practiced by solving all problem steps and those who practiced by solving a gradually increasing number of steps starting with the first step first (forward-fading practice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 42 publications
0
34
0
Order By: Relevance
“…One interesting direction in the context of technical literacy education is to examine the integration of equations and circuit diagrams in the context of instructional strategies based on worked examples, which have received growing interest [47]- [49]. Another direction is to examine the integration of equations into circuit diagrams in the context of more complex circuit analysis taught to engineering majors.…”
Section: Future Directionsmentioning
confidence: 99%
“…One interesting direction in the context of technical literacy education is to examine the integration of equations and circuit diagrams in the context of instructional strategies based on worked examples, which have received growing interest [47]- [49]. Another direction is to examine the integration of equations into circuit diagrams in the context of more complex circuit analysis taught to engineering majors.…”
Section: Future Directionsmentioning
confidence: 99%
“…Reviews by Azevedo and Bernard (1995) as well as Mason and Bruning (2001) have similarly found benefits of immediate feedback for learning problem solving. Studies by Dihoff, Brosvic, Epstein, and Cook (2004) for the domain of preparation for general factual knowledge tests, and recently by Moreno, Reisslein, and Ozogul (2009) in the engineering problem solving domain, as well as Lin, Lai, and Chuang, (2013) on database concepts found also that immediate (timely) feedback after individual problem steps leads to improved learning compared to delayed feedback that is given after a learner has attempted to solve an entire multi-step problem. Van der Kleij, Eggen, Timmers, and Veldkamp (2012) in their examination of students learning economics facts found that students paid closer attention to immediate feedback than to delayed feedback.…”
Section: Immediate Feedbackmentioning
confidence: 97%
“…The diagram was represented with conventional abstract electrical engineering symbols (Johnson, Reisslein, & Reisslein, 2013;Reisslein, et al, 2010). The prompts for entering the solution attempts and the corresponding corrective and explanatory feedback (Moreno, 2004;Moreno & Mayer, 2007;Moreno, et al, 2009) were displayed in the bottom half of the screen.…”
Section: Apparatusmentioning
confidence: 99%
“…First, authoring tools for video creation continue to increase in power and ease of use, while simultaneously dropping in price. Second, the research on the worked-example effect [1]- [3] continues to support the notion that video-based worked examples can be effective instructional supports for novice learners. The coalescence of these two factors has led to the ubiquity of instructional videos available online across a huge range of topics.…”
Section: Introductionmentioning
confidence: 94%